IMPLEMENTASI ETIKA BISNIS ISLAM TERHADAP SISTEM RESELLER DAN RELEVANSINYA DALAM UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Azhar Alam; Sri Herianingrum; Tata Leni Lestari; Aditya Nurrahman (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
This study is to find out about the practice of the reseller system at Beteng Trade Center and to find out the implementation of Islamic business ethics on the reseller system at Beteng Trade Center and its relevance in the Consumer Protection Act (UUPK). Primary data sources were obtained through interviews with two suppliers, ten resellers, and three consumers. This study's secondary data sources were obtained from various literature, laws, and regulations. This study shows that the reseller system mechanism at Beteng Trade Center uses an indirect distribution strategy and has met the requirements of the reseller system. The implementation of Islamic business ethics on the reseller system has fulfilled the rights of consumers and the obligations of business actors following the principles of Islamic business ethics in the form of honesty, fairness, trustworthiness, openness, and no element of fraud. Consumer protection in the reseller system at Beteng Trade Center is by UUPK because it meets the rules of UUPK Article 4 No 8, Article 4 letter D, Article 7 letter F and Article 7 letter D regarding consumer protection. This research can be a reference for managing reseller systems and applying Islamic business ethics associated with consumer protection laws. This research contributes to the analysis of Islamic business ethics in the application of the reseller system and the study of related consumer protection laws.